(untitled) (Journal of Comparative Social Work, 2012)
A qualitative research study was conducted in northern Canada in 2007 which examined the realities and issues surrounding palliative care with seniors in remote northern settings. As a profession with a recognized role in supporting those who are dying and those who are bereaved, social work has been integral to the development of palliative care support services in northern Canada. However, in regions of the North where the social work profession is less developed and less recognized, the role for social work remains understated.